Mimicking T- shaped giant meckel’s diverticulum: another rare anatomical variant complicating small bowel obstruction by adhesions - Mannan, Ambreen; Alshumari, Osama A. E. (International Surgery Journal, 2018)
We report case with Meckel’s diverticulitis complicated by adhesive intestinal obstruction. An adolescent of 13-yr-old boy with history of recurrent right sided lower abdominal pain and vomiting for two days. According to his mother he had been suffering this type of pain intermittently for last three years which was treated conservatively. This time the pain was out of proportion therefore she reported in tertiary hospital. On examination patient was tender at right iliac fossa region with abdominal guarding. CT scan of abdomen revealed multiple fluid-filled, dilated proximal bowel loops. Meckel’s diverticulum was not suspected until diagnostic laparoscopy was performed. Patient was converted to open laparotomy where the giant (13 cm sized), narrow base mimicking T-shaped Meckel’s diverticulum and inter bowel loop adhesions near terminal ileum were seen. About 20 cm affected ileal segment with Meckel’s diverticulum resected and primary end to end anastomosis performed. The postoperative course remained uneventful. Histopathology report confirms the inflammation of Meckel’s diverticulum. Significance of this type of Meckel’s diverticulum is its T-shaped mimicking appearance with giant size body and narrow base and was manifested with recurrent sub occlusive intestinal obstruction in the period of three years. It is the second ever reported case in English journals.